2017
DOI: 10.1016/s2213-8587(17)30103-1
|View full text |Cite
|
Sign up to set email alerts
|

Effect of monthly high-dose vitamin D supplementation on falls and non-vertebral fractures: secondary and post-hoc outcomes from the randomised, double-blind, placebo-controlled ViDA trial

Abstract: Health Research Council of New Zealand and Accident Compensation Corporation of New Zealand.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
147
0
6

Year Published

2017
2017
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 174 publications
(159 citation statements)
references
References 28 publications
6
147
0
6
Order By: Relevance
“…For example, a Mendelian randomization study suggested that the association between genetically low vitamin D status and areal BMD was not causal [3], which agrees with the effect of vitamin D supplementation on areal BMD [4] and would be compatible with compensatory adaptation of bone to mechanical strain that is a prominent mechanism in the skeleton [5][6][7]. Furthermore, in the randomized, double-blind, placebo-controlled ViDA trial, monthly high-dose vitamin D supplementation of 100 000 IU colecalciferol for 3-4 years did not change the risk of fractures, and the result was independent of baseline S-25OHD levels including even less than 25 nmol L À1 and over 75 nmol L À1 [8]. The same interpretation can be applied to observational studies showing the association between use of proton pump inhibitors and an increased risk of hip fracture [9,10].…”
mentioning
confidence: 80%
“…For example, a Mendelian randomization study suggested that the association between genetically low vitamin D status and areal BMD was not causal [3], which agrees with the effect of vitamin D supplementation on areal BMD [4] and would be compatible with compensatory adaptation of bone to mechanical strain that is a prominent mechanism in the skeleton [5][6][7]. Furthermore, in the randomized, double-blind, placebo-controlled ViDA trial, monthly high-dose vitamin D supplementation of 100 000 IU colecalciferol for 3-4 years did not change the risk of fractures, and the result was independent of baseline S-25OHD levels including even less than 25 nmol L À1 and over 75 nmol L À1 [8]. The same interpretation can be applied to observational studies showing the association between use of proton pump inhibitors and an increased risk of hip fracture [9,10].…”
mentioning
confidence: 80%
“…Therefore, it is one of the most frequently used ‘drugs’ in the world. A large RCT (VIDA) recently demonstrated that monthly doses of vitamin D3, equivalent to about 3000 IU per day for 3.4 years., did not reduce the risk of nonvertebral fractures . Fractures were only a secondary end‐point, and the study was not fully powered to answer the question of antifracture efficacy.…”
Section: Biochemical and Clinical Implications Of Vitamin D Statusmentioning
confidence: 99%
“…There was no difference in falls between vitamin D and placebo over up to 4 years of follow up. Reported falls were 1312 (52%) vitamin D vs. 1326 (53%) placebo; HR=0.99 (0.92, 1.07) p=0.82 [27,28].…”
Section: Finally Dr Moray Campbell (Ohio State University) Examined mentioning
confidence: 97%